Soil Microbial Functional and Fungal Diversity as Influenced by Municipal Sewage Sludge Accumulation - Frąc, Magdalena (MDPI, 2014)
Safe disposal of municipal sewage sludge is a challenging global environmental concern. The aim of this study was to assess the response of soil microbial functional diversity to the accumulation of municipal sewage sludge during landfill storage. Soil samples of a municipal sewage sludge (SS) and from a sewage sludge landfill that was 3 m from a SS landfill (SS3) were analyzed relative to an undisturbed reference soil. Biolog EcoPlates(TM) were inoculated with a soil suspension, and the Average Well Color Development (AWCD), Richness (R) and Shannon-Weaver index (H) were calculated to interpret the results. The fungi isolated from the sewage sludge were identified using comparative rDNA sequencing of the LSU D2 region. The MicroSEQ® ID software was used to assess the raw sequence files, perform sequence matching to the MicroSEQ® ID-validated reference database and create Neighbor-Joining trees. Moreover, the genera of fungi isolated from the soil were identified using microscopic methods. Municipal sewage sludge can serve as a habitat for plant pathogens and as a source of pathogen strains for biotechnological applications.